Design of a New Ultracompact Resonant Plasmonic Multi-Analyte Label-Free Biosensing Platform - Francesco Dell’Olio; Donato Conteduca; Maripina De Palo; Caterina Ciminelli (Sensors, 2017)
In this paper, we report on the design of a bio-multisensing platform for the selective label-free detection of protein biomarkers, carried out through a 3D numerical algorithm. The platform includes a number of biosensors, each of them is based on a plasmonic nanocavity, consisting of a periodic metal structure to be deposited on a silicon oxide substrate. Light is strongly confined in a region with extremely small size (=1.57 μm2), to enhance the light-matter interaction. A surface sensitivity Ss = 1.8 nm/nm has been calculated together with a detection limit of 128 pg/mm2. Such performance, together with the extremely small footprint, allow the integration of several devices on a single chip to realize extremely compact lab-on-chip microsystems. In addition, each sensing element of the platform has a good chemical stability that is guaranteed by the selection of gold for its fabrication.